Tubuh Kebangkitan dan Luka yang Memulihkan: Refleksi Teologis atas Trauma dan Pemulihan - Tickos Elia Siahaan (Nubuat : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
This article explores theological perspectives on the resurrection of Christ that still feature wounds as a meaningful way to understand and heal trauma. The wounds of Christ that remain after his resurrection are a sign of hope, healing, and reconciliation. In a digital age filled with violence and trauma, the meaning of the resurrection of the body conveys the message that wounds are not the end of everything, but rather part of a holistic healing process both physically, mentally, and spiritually. The incarnation and solidarity of God through the suffering of Christ show that God is present in human grief. The community of faith and pastoral care also have a crucial role in addressing those who have experienced trauma. With a holistic approach that combines body, soul, and spirit, the resurrected body of Christ becomes an example of healing and a source of strength for wounded individuals.